SITE MAKES HARLEY DAVIDSON USING MACROMEDIA DREAMWEAVER - Dessy Caprina; Linda Wahyu Widianti, Skom, MMsi (Jurnal Sistem Informasi, 2005)
Today technology is growing rapidly berkembangan which men need lots of fast-paced information. Especially with the internet facility which began ogled as a media campaign that was quite interesting. To the writer want to provide news and information about Harley -Davidson Motor Shhowroom without having to visit them. And also this site is created by using the Indonesian language so that the fan motors will be more easily understood.